(untitled) (International Educators Conference, 2025)
This article provides characteristics of zoned varieties of vegetable soybeans included in the State Register of Agricultural Crops of Uzbekistan, recommended for cultivation in the territory of the Republic of Uzbekistan, and also developed sowing periods for repeated vegetable crops.